Folkways Lonto Leok Budaya Manggarai dalam Terang Pemikiran William Sumner Tentang Masyarakat Sebagai Kerjasama Antagonistic - Mathias Jebaru Adon (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
As a large nation consisting of various regional cultures, Indonesia has various folkways, which are the skills and local wisdom of the Indonesian people. In Manggarai culture, one folkway that is most famous is lonto leok. Lonto leok is the life principle of the Manggarai community which expresses a sense of unity and oneness as a group of people. Therefore, this study aims to reveal the value of togetherness contained in folkways lonto leok. The methodology used is an interpretive method of the phenomenon of living with the Manggarai community in a comparative study with William Graham Sumner's thinking about society as an antagonistic collaboration. This study reveals that the Manggarai community was born from the antagonistic collaboration between tribes who fought each other in the past, which then united to form the Manggarai community as it is today. These historical traces are clearly revealed in the folkways lonto leok, which means collective deliberation. This study contributes to understanding the history of the unity of the Republic of Indonesia and how this unity is maintained.